English language teaching and teacher education in East Asia global challenges and local responses - Tsui, Amy B. M. 1950- (Cambridge education research, 2021)
The spread of English is so much an integral part of globalization that it has become an essential global literacy skill. In Asia, this poses immense challenges to governments and English language teaching and teacher education professions as they attempt to meet this demand from students for a high level of English proficiency. This volume examines English language education policies across ten Asian jurisdictions, the corresponding teacher education policies, and how these policies affect teachers and teacher educators. Each chapter covers a different jurisdiction, and is written by a scholar engaged in the implementation of government policies on English language and teacher education, providing the reader with insiders' perspectives. It gives a fascinating glimpse into the remarkable similarities in the challenges posed to these countries and the critical issues that have emerged from the local responses despite their markedly different socioeconomic, political, cultural and historical backgrounds